2020
DOI: 10.3389/fchem.2020.570185
|View full text |Cite
|
Sign up to set email alerts
|

Glycoconjugations of Biomolecules by Chemical Methods

Abstract: Bioconjugations under benign aqueous conditions have the most promise to covalently link carbohydrates onto chosen molecular and macromolecular scaffolds. Chemical methodologies relying on C-C and C-heteroatom bond formations are the methods of choice, coupled with the reaction conditions being under aqueous milieu. A number of methods, including metal-mediated, as well as metal-free azide-alkyne cyclo-addition, photocatalyzed thiol-ene reaction, amidation, reductive amination, disulfide bond formation, conjug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 101 publications
0
21
0
Order By: Relevance
“…Fluorescein‐labelled lectins (AAL and SBA), SBA‐Alexa Fluor (488 conjugate), and BSA‐conjugated monosaccharides (L‐fucose, D‐galactose, and N ‐acetyl‐D‐galactosamine) were purchased from Vector Labs (Burlingame, CA). The monosaccharides were modified by vinyl sulfone at the anomeric carbon and subsequently conjugated to BSA [51,52] …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fluorescein‐labelled lectins (AAL and SBA), SBA‐Alexa Fluor (488 conjugate), and BSA‐conjugated monosaccharides (L‐fucose, D‐galactose, and N ‐acetyl‐D‐galactosamine) were purchased from Vector Labs (Burlingame, CA). The monosaccharides were modified by vinyl sulfone at the anomeric carbon and subsequently conjugated to BSA [51,52] …”
Section: Methodsmentioning
confidence: 99%
“…The monosaccharides were modified by vinyl sulfone at the anomeric carbon and subsequently conjugated to BSA. [51,52] Synthesis of cyclic Ala scan analogues. The linear peptidyl-resin precursors for naturally occurring OL peptide 1 and its Ala scan analogues (2-17) were synthesized using TentaGel XV RAM resin (substitution 0.27 mmol/g, 0.1 mmol scale) and standard Fmoc-SPPS on a PS3 automated peptide synthesizer (Protein Technologies Inc., Tucson, AZ).…”
Section: Methodsmentioning
confidence: 99%
“…[ 57 ] The N‐hydroxysuccinimide (NHS) was used in order to form the stable NHS ester in situ as one of the three ways by adding EDC, otherwise, o‐acylisourea by contact with H 2 O results into regenerated carboxyl group by hydrolysis. [ 50 ] As a result, the EDC‐HCl as the 1 st increment and NHS as the 2 nd (with ratio for Ia as 63.789:95.750 mg, Ib as 60.410:90.680 mg, Ic as 49.622:74.484 mg, respectively) were added into aMES/NMs solution (20 ml) for incubation (20 minutes, 25°C). The dispersed IIa , IIc in H 2 O (10 ml) by sonication were added into aMES (10 ml).…”
Section: Experimental Section/methodsmentioning
confidence: 99%
“…The biochemical studies showed further that the glycoconjugated protein retained the antimicrobial activities as that of the native lysozyme. [63] In a plethora methods known for glycoconjugations of biomolecules, [64,65] the benign nature of the newly developed methodology lies in the reaction being reagent-less, pending to only a basic pH of the solution.…”
Section: P E R S O N a L A C C O U N T T H E C H E M I C A L R E C O R Dmentioning
confidence: 99%